EXPERIMENTAL STUDY THROUGH DESIGNS PRODUCED IN NON-REMOVABLE FORMWORK - , Л. І., О. І., Н. М. (Municipal economy of cities. Series: «Economy science», 2013)
Information on experimental studies of cross-cutting structures made of non-removable formwork.